Non-conscious visual cues related to affect and action alter perception of effort and endurance performance - Blanchfield, Anthony; Hardy, James; Marcora, Samuele (Frontiers in Human Neuroscience, 2014)
The psychobiological model of endurance performance proposes that endurance performance is determined by a decision-making process based on perception of effort and potential motivation. Recent research has reported that effort-based decision-making during cognitive tasks can be altered by non-conscious visual cues relating to affect and action. The effect of these non-conscious visual cues on effort and performance during physical tasks is however unknown. We report two experiments investigating the effect of subliminal priming with visual cues related to affect and action on perception of effort and endurance performance. In Experiment 1 thirteen individuals were subliminally primed with happy or sad faces as they cycled to exhaustion in a counterbalanced and randomized crossover design. A paired t-test (happy vs. sad faces) revealed that individuals cycled for significantly longer (178 s, p = .04) when subliminally primed with happy faces. A 2 x 5 (condition x iso-time) ANOVA also revealed a significant main effect of condition on rating of perceived exertion (RPE) during the time to exhaustion (TTE) test with lower RPE when subjects were subliminally primed with happy faces (p = .04). In Experiment 2, a single-subject randomization tests design found that subliminal priming with action words facilitated a significantly longer (399 s, p = .04) TTE in comparison to inaction words (p = .04). Like Experiment 1, this greater TTE was accompanied by a significantly lower RPE (p = .03). These experiments are the first to show that subliminal visual cues relating to affect and action can alter perception of effort and endurance performance. Non-conscious visual cues may therefore influence the effort-based decision-making process that is proposed to determine endurance performance. Accordingly, the findings raise notable implications for individuals who may encounter such visual cues during endurance competitions, training, or health related exercise.